Post American World - Fareed Zakaria; ZAKARIA (Fareed) (New Delhi Viking, 2008)
"This is not a book about the decline of America, but rather about the rise of everyone else." So begins Fareed Zakaria's important new work on the era we are now entering. Following on the success of his best-selling The Future of Freedom, Zakaria describes with equal prescience a world in which the United States will no longer dominate the global economy, orchestrate geopolitics, or overwhelm cultures. He sees the "rise of the rest"$1 (Bthe growth of countries like China, India, Brazil, Russia, and many others$1 (Bas the great story of our time, and one that will reshape the world. The tallest buildings, biggest dams, largest-selling movies, and most advanced cell phones are all being built outside the United States. This economic growth is producing political confidence, national pride, and potentially international problems. How should the United States understand and thrive in this rapidly changing international climate? What does it mean to live in a truly global era? Zakaria answers these questions with his customary lucidity, insight, and imagination.s
Keywords: Social Process; International Relations; World Politics